Development of Management Information Systems In The Digital Era - Halim Wijaya; Muhammad Irwan Padli Nasution (Yayasan Bayt Shufiya Nusantara, 2025)
Technological transformation in the digital era encourages organizations to adopt Management Information Systems (MIS) that are increasingly responsive, integrated, and data-driven. This study aims to analyze how MIS development is carried out in the digital era and identify the factors that influence its successful implementation. The research method applies a literature review combined with descriptive analysis of contemporary system development models, including the use of cloud computing, big data analytics, and the integration of web-based platforms with mobile applications. The findings indicate that modern MIS development is not limited to improving operational efficiency but also focuses on the ability of systems to generate real-time information, enhance service quality, and strengthen organizational adaptability in responding to rapid business dynamics. The study also highlights that the success of MIS implementation is strongly affected by human resource competence, information security readiness, and the maturity of information technology governance within the organization. Overall, this research concludes that organizations must adopt sustainable MIS development strategies, prioritize continuous improvement, and encourage innovation to remain competitive in the face of digital transformation. A proactive approach to technology adoption and effective governance becomes essential for maximizing the strategic value of MIS in the modern business environment.